ANALISIS KINERJA KEUANGAN BANK UMUM KONVENSIONAL KBMI 3 TAHUN 2017-2022 - Trisnawati, Luh Putu Puji; Alfayed, Jonathan Tristan (JURNAL LENTERA AKUNTANSI, 2024)
In general, the purpose of an established company is to make a profit for its owners. A company that performs well can generate high profits with a long period of time and is able to attract investors to invest its funds. One form of information that can be used to determine the condition and development of a company is the financial statements reported at the end of each period as a report on management accountability for the management of a company. Company performance is a description of the financial condition of a company that is analyzed with various financial analysis tools, so that it can be known about the good and bad financial condition of a company that reflects performance achievements in a certain period. This study aims to analyse the financial performance of core capital group (KMBI) 3 banks using Otoritas Jasa Keuangan (OJK) report data for the period 2017 - 2022 which is processed using the Eviews application. The results of the study found that Capital Adequacy Ratio (CAR) has a significant positive influence on company performance in this case Return On Asset, Non Performing Loan (NPL) does not have a significant effect on Return On Asset, Loan To Deposit Ratio (LDR) has a significant positive influence on Return On Asset and Operating Expense to Opeating Income (BOPO) has a significant negative influence on Return On Asset. Key words: Financial Performance, Commercial Banks, Core Capital Bank Group 3